Analisis Penerapan Koreksi Fiskal Atas Pendapatam Dan Beban Dalam Laporan Keuangan Komersial serta Menghitung PPh Terutang PT. Andretty - Muhammad Zaki Mubarok (SUSTAINABLE JURNAL AKUNTANSI, 2021)
Tax is an obligation of every citizen who legally has fulfilled the tax obligations based on the law of Indonesia. Tax collection by the state either through the central government or local government will certainly have an impact on reducing the income or wealth of each individual taxpayer and corporate taxpayer who pays it, but in essence the tax paid is an income whose benefits will return again to the taxpayers. This return can be in the form of routine expenditures and development expenditures carried out by the state. PT. Andretty is a company engaged in LPG Gas Distributor whose distribution area includes Surabaya and Gresik. PT Andretty is a Corporate Taxpayer who has to do the calculation, reporting, and deposit on the tax payable. The method used in this research is qualitative with a descriptive approach. The data are collected by observation and documentation method. The data analysis technique used is descriptive qualitative. The data consist of primary data and secondary data. The results of this research indicate that taxpayers have implemented fiscal corrections in accordance with applicable regulations, but there are still some errors related to fiscal corrections of income and expenses that have not been corrected properly. For that reason researcher has tried to recalculate the income statement fiscal PT. Andretty and the Taxpayers have calculated the Tax Payable in accordance with the proper rules. There is an underpayment difference between the calculation made by the Taxpayer and the Researcher. The tax payable should be Rp.460.750.690. Therefore, in the future the Taxpayer needs to be more careful to apply fiscal corrections to income and expenses in the Fiscal Income Statement and calculate the Income Tax payable correctly.